TINDAK PIDANA PENCEMARAN NAMA BAIK Oleh WARTAWAN MELALUI MEDIA SOSIAL - Amalia, Rifda; Setyorini, Erny Herlin (Journal Evidence Of Law, 2023)
Developments regarding technology and information are illustrated by the existence of internet media devices that can be controlled by electronic devices including computers. Technology has an important impact on the understanding of criminal acts, especially schools of criminology which emphasize the object factors in the form of humans, which are seen physically and psychologically. One of the crimes by abusing technological advances that are electronic and information is defamation of the good name of other parties on social media through electronic media devices. Freedom of opinion is seen in Article 28 (1) of the 1945 Constitution of the Unitary State of the Republic of Indonesia. However, there are also prohibitions to prevent defamation. The arrangement is contained in the Criminal Code (KUHP). There are also various laws providing regulations regarding acts of defamation of names. In addition to the lex generalis provisions in criminal law, there are also lex specialis provisions in non-criminal law, namely Law number 19 of 2016 concerning amendments to Law number 11 of 2008 concerning Information and Electronic Transactions, Law Number 40 of 1999 concerning the Press, and Law Number 32 of the year 2002 Regarding Broadcasting.